"How Should I Tell my Child?" Disclosing the Diagnosis of Sex Chromosome Aneuploidies. Issue 1 (3rd September 2014) - Dennis, Anna; Howell, Susan; Cordeiro, Lisa; Tartaglia, Nicole
Abstract: To date, the disclosure of a sex chromosome aneuploidy (SCA) diagnosis to an affected individual has not been explored. This study aimed to assess the timing and content revealed to an affected child by his or her parent(s), resources accessed in preparation, parental feelings of preparedness, common parental concerns, and recommendations for disclosure approaches. Two online surveys were created: 1) for parents of a child with a diagnosis and 2) for individuals with a diagnosis. One‐hundred thirty‐nine parent surveys (XXY n = 68, XXX n = 21, XYY n = 9, other SCAs n = 41) and 67 individual surveys (XXY n = 58, XXX n = 9) were analyzed. Parents most frequently discussed the topics of learning disabilities (47 %) and genetics (45 %) with their child during the initial disclosure. A significantly greater proportion of parent respondents reported feeling prepared vs. unprepared for disclosure, regardless of their child's diagnosis (z‐test of proportions, all p 's < 0.001). Both prepared and unprepared parents most frequently accessed resources such as websites, support groups, and discussion with the child's physician prior to disclosure, with unprepared parents accessing fewer resources ( M = 2.0 ± 1.41) than prepared parents [ M = 2. ± 1.56; t(101) =−2.02, p < 0.05]. Common parental concerns included making the conversation age‐appropriate, discussing infertility, and possible impact on the child's self‐esteem. Both parent and individual respondents endorsed being honest with the child, disclosing the diagnosis early and before puberty, and discussing the diagnosis gradually over time. These results provide recommendations for parents, and suggest benefits from additional resources and supports to alleviate concerns when approaching diagnosis disclosure.